Nnimmo Bassey’s Aesthetic Imagination and Social Meaning in We Thought It Was Oil but It Was Blood - Okwudiri Anasiudu (Universitas Sanata Dharma, 2022)
This paper explores Nnimmo Bassey’s poetry collection: We Thought it Was Oil but It Was Blood. It interrogates the aesthetic imagination and language use in the construction of the poem as a text, and the social meaning wrapped in such imagination and language use. This paper draws insight from postcolonial ecocriticism and critical functional linguistics as theoretical frameworks. The methodology this paper adopts is qualitative, descriptive, and critical. The guiding motivation for this research is the dearth of critical study on Bassey’s We Thought it Was Oil but It Was Blood. The research problem and gap this study seeks to bridge is the minimal attention the available scholarship on Bassey's poetry offered to the exploration of aesthetic imagination and social meaning construed through the internal formal structure of the poem, realised through stanzas, and structures and the linguistic configuration such as deixis, metaphorical schemas. The analysis shows that place deixis, pronouns adjective, and metaphors are important linguistic designs Bassey deploys in construing his aesthetic imagination, particularly the social realities of the Niger Delta region such as the contentious issue of environmental justice, ecological despoliation, minority rights, and agitation whenever resource control is mentioned.